LINKING REMUNERATION STRATEGIES TO EMPLOYEE ENGAGEMENT AND PRODUCTIVITY: EVIDENCE FROM MERIT PAY, BONUSES, AND GAIN SHARING SCHEMES - Oyedele, Oloruntoba (J-MACC : journal of management and accounting, 2025)
This study examines the relationship between four performance-based pay mechanisms, including merit pay, individual performance bonuses, gain sharing, and group performance incentives, and employee work behaviour. Using statistical analysis, the results reveal strong and significant correlations across all mechanisms, with coefficients of determination ranging from 0.726 to 0.898 and significance levels well below the 0.01 threshold. The findings reject the null hypotheses in all cases, indicating that performance-linked remuneration systems substantially influence employee behavioural outcomes, including work engagement, punctuality, teamwork, and reductions in counterproductive behaviour. Respondent feedback further corroborates the quantitative results, highlighting that merit pay motivates performance improvements across all employee levels, individual bonuses foster engagement and reduce absenteeism, and gain sharing promotes commitment and willingness to exceed role expectations. While group performance incentives enhance collaboration, they may also risk demotivating top performers when individual contributions are overlooked. The study concludes that integrating diverse performance-based pay strategies can positively shape employee behaviour, though organisations must manage fairness perceptions to maximise their effectiveness.